2009
DOI: 10.1103/physreva.80.022901
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal Casimir-Polder potentials of ground-state polar molecules in a planar cavity

Abstract: We analyze the thermal Casimir-Polder potential experienced by a ground-state molecule in a planar cavity and investigate the prospects for using such a setup for molecular guiding. The resonant atom-field interaction associated with this nonequilibrium situation manifests itself in oscillating standing-wave components of the potential. While the respective potential wells are normally too shallow to be useful, they may be amplified by a highly reflecting cavity whose width equals a half-integer multiple of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…For this reason Re[G zz (z, ω o )] decays much faster than Re[G xx,yy (z, ω o )]. In reality this term will dominate the far field of CP interaction for excited state atoms or molecules [40,41]. At very large temperatures or at very large distances from the surface it will eventually dominate the interaction between a surface and a ground state atom.…”
Section: Far Field Approximationmentioning
confidence: 99%
“…For this reason Re[G zz (z, ω o )] decays much faster than Re[G xx,yy (z, ω o )]. In reality this term will dominate the far field of CP interaction for excited state atoms or molecules [40,41]. At very large temperatures or at very large distances from the surface it will eventually dominate the interaction between a surface and a ground state atom.…”
Section: Far Field Approximationmentioning
confidence: 99%
“…Care must also be taken with the m = 0 term in the cosine series. The result of a straightforward calculation leads to dζ 2π 14) where the term divergent as ξ → 1 may, through a similar calculation, be shown to be that corresponding to the vacuum in absence of the wedge, that is, that obtained from the free Green's dyadic. Therefore, we must subtract this term off, to obtain the static Casimir energy (7.7), which for this situation is…”
Section: Wedge Calculationmentioning
confidence: 99%
“…From this, we can work out the energy of the system from 14) where the factor of 1/2 comes from the fact that this must be the energy required to assemble the system. In computing this energy we must, of course, drop the self-energy of the dipole due to its own field.…”
Section: Three Dimensional Aperture Interacting With Dipolementioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that even ground state particles are subject to an oscillating force component in the presence of macroscopic bodies at nonzero temperature. While utterly unobservable for atoms (which are essentially in their ground state when thermalized at room temperature), there could be some hope of observing and even using this effect for molecules, 11,12 which have excited states of very low energy. A similar investigation was recently made 13 by applying Keldysh theory to the system of two atoms prepared in an arbitrary state, in the presence of an external (thermal) electromagnetic field.…”
mentioning
confidence: 99%